Utility of CSF IL-6 monitoring in managing ICANS associated with Epcoritamab treatment: a case report and literature review - Takahata, Atsushi; Akita, Kaori; Shimada, Tomohito; Bando, Kana; Toyota, Shigeo (Journal of Clinical and Experimental Hematopathology, 2025)
Immune effector cell-associated neurotoxicity syndrome (ICANS) is a serious complication observed in patients receiving advanced immunotherapies such as bispecific antibodies and CAR-T cell therapies. Although the Immune Effector Cell-Associated Encephalopathy (ICE) score is commonly used to assess ICANS severity, its diagnostic accuracy can be compromised by factors such as concomitant medications, underlying comorbidities, and other external influences. This case report discusses a patient with diffuse large B-cell lymphoma who developed ICANS while receiving Epcoritamab. Notably, elevated interleukin-6 (IL-6) levels in the cerebrospinal fluid (CSF) correlated with the patient’s clinical course of neurotoxicity. In contrast to conventional scoring systems, which can be affected by unrelated factors, CSF IL-6 levels appeared to more directly reflect the severity and progression of ICANS. These findings are consistent with similar reports from patients treated with CAR-T cells, suggesting that CSF IL-6 may serve as a reliable marker for ICANS progression. Further research that systematically measures CSF IL-6 in diverse clinical contexts could help validate its role as a biomarker, enhancing diagnostic precision and guiding optimal management strategies for ICANS.